Recent progress on three-dimensional nanoarchitecture anode materials for lithium/sodium storage. (20th August 2022) - Zhang, Zhijia; Chen, Yuefang; Sun, Shihao; Sun, Kai; Sun, Heyi; Li, Hongwei; Yang, Yuhe; Zhang, Mengmeng; Li, Weijie; Chou, Shulei; Liu, Huakun; Jiang, Yong
Highlights: 3D nanostructure anode materials have efficient electron/ion transport paths. 3D nanoarchitecture is expected to realize the nanomaterials' practical application. High-performance lithium-ion batteries are urgently needed in energy storage. Sodium-ion batteries are being at the critical point of an industrial explosion. Abstract: High-performance batteries with high density and low cost are needed for the development of large-scale energy storage fields such as electric vehicles and renewable energy systems. The anode with three-dimensional (3D) nanoarchitecture is one of the most attractive candidates for high-performance lithium-ion batteries (LIBs) and sodium-ion batteries (SIBs) due to its efficient electron/ion transport and high active material mass loading. Although some important breakthroughs have been made in 3D nanoarchitecture anode materials, more improvements are still needed for high cycling stability and high energy density. Herein, the latest research progress of 3D nanoarchitecture anode materials for LIBs and SIBs is reviewed, including nanoporous metal, nanoporous graphene, and their derived foams. Specifically, the storage properties of Li/Na ions, the kinetics of ion/electron transport, and specific chemical interactions are discussed based on the structure design. In addition, the research strategies and structural characteristics of 3D nanoarchitecture anode materials are summarized, providing a reference for the further development of LIBs and SIBs. Meanwhile, the future research directions of LIBs and SIBs have also prospected.